High plasma adiponectin levels are associated with frailty in a general old‐old population: The Septuagenarians, Octogenarians, Nonagenarians Investigation with Centenarians study. Issue 6 (2nd February 2018) - Nagasawa, Motonori; Takami, Yoichi; Akasaka, Hiroshi; Kabayama, Mai; Maeda, Satomi; Yokoyama, Serina; Fujimoto, Taku; Nozato, Yoichi; Imaizumi, Yuki; Takeda, Masao; Itoh, Norihisa; Takeya, Yasushi; et al.
Abstract : Aim: The objective of the present study was to investigate the association between frailty and plasma adiponectin levels in a general population of Japanese older adults. Methods: The volunteer older adults, aged approximately 83 years, were recruited randomly from a general population in the Japanese Septuagenarians, Octogenarians, Nonagenarians Investigation with Centenarians study. We used the modified Cardiovascular Health Study criteria to assess the frailty status of the study participants. The study participants were classified as non‐frail, pre‐frail and frail according to their physical activities. We compared plasma adiponectin levels among these three groups and applied a multivariate logistic regression analysis including plasma adiponectin levels to clarify the factors associated with frailty status in the cross‐sectional design. Results: The mean age of the participants was 83.1 ± 0.9 years, and 51.8% were men. The frailty index was available to assess 353 participants, of whom 24.6% were classified as non‐frail, 62.3% as prefrail and 13.0% as frail. The log‐transformed plasma adiponectin levels increased stepwise in the following order: non‐frail, pre‐frail and frail. A multivariate logistic regression analysis showed that higher plasma adiponectin levels, a higher estimated glomerular filtration rate and lower hemoglobin levels were independent determinants for pre‐frail/frail status compared with non‐frail status. Conclusions: The present study showed that higher plasma adiponectin levels were associated with frailty status in older Japanese adults in the general population. Further longitudinal study is essential to clarify the role of plasma adiponectin in the progression of frailty.Geriatr Gerontol Int 2018; 18: 839–846